2020
DOI: 10.3389/fpls.2020.01213
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among the Rootstock, Crop Load, and Sugar Hormone Signaling of Apple Tree, and Their Effects on Biennial Bearing

Abstract: Adjustable crop load primarily involves bud manipulation, and usually switches from vegetative to reproductive buds. While this switch is not fully understood, it is still controlled by the ratio of hormones, which promote or inhibit bud formation. To determine the reasons for biennial bearing, the effect of apple rootstock, scion cultivar, crop load, as well as metabolic changes of endogenous phytohormones [zeatin, jasmonic acid, indole-3 acetic acid (IAA), abscisic acid (ABA), and gibberellins 1, 3, and 7 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
(105 reference statements)
1
15
1
2
Order By: Relevance
“…Hass plantations may confer a beneficial horticultural quality to the tree across a wide spectrum of traits ( Reyes-Herrera et al, 2020 ), such as increased fruit yield ( Herrera-González et al, 2013 ), postharvest performance ( Willingham et al, 2001 ), vegetative vigor ( Mickelbart and Arpaia, 2002 ), salt tolerance ( Bernstein et al, 2001 ), and disease resistance ( Smith et al, 2011 ; Sánchez-González et al, 2019 ). These reports are in line with previous research that have shown how rootstocks might also induce less trivial scion morphological changes, such as dwarfing, and even alter yield traits and fruit quality ( Egea et al, 2004 ; Picolotto et al, 2010 ; Madam et al, 2011 ; Expósito et al, 2020 ; Kviklys and Samuoliene, 2020 ). For instance, rootstock effects may even influence properties typically attributed to the clonal Hass scion, such as fruit sensorial and nutritional quality, e.g., texture, sugar content, acidity, pH, flavor, and color ( Giorgi et al, 2005 ; Gullo et al, 2014 ; Balducci et al, 2019 ), cold tolerance, and shoot pest and pathogen resistance ( Rubio et al, 2005 ; Goldschmidt, 2014 ).…”
Section: Introductionsupporting
confidence: 91%
“…Hass plantations may confer a beneficial horticultural quality to the tree across a wide spectrum of traits ( Reyes-Herrera et al, 2020 ), such as increased fruit yield ( Herrera-González et al, 2013 ), postharvest performance ( Willingham et al, 2001 ), vegetative vigor ( Mickelbart and Arpaia, 2002 ), salt tolerance ( Bernstein et al, 2001 ), and disease resistance ( Smith et al, 2011 ; Sánchez-González et al, 2019 ). These reports are in line with previous research that have shown how rootstocks might also induce less trivial scion morphological changes, such as dwarfing, and even alter yield traits and fruit quality ( Egea et al, 2004 ; Picolotto et al, 2010 ; Madam et al, 2011 ; Expósito et al, 2020 ; Kviklys and Samuoliene, 2020 ). For instance, rootstock effects may even influence properties typically attributed to the clonal Hass scion, such as fruit sensorial and nutritional quality, e.g., texture, sugar content, acidity, pH, flavor, and color ( Giorgi et al, 2005 ; Gullo et al, 2014 ; Balducci et al, 2019 ), cold tolerance, and shoot pest and pathogen resistance ( Rubio et al, 2005 ; Goldschmidt, 2014 ).…”
Section: Introductionsupporting
confidence: 91%
“…Histological analysis has shown that the initial development of a flower bud coincides with a developing embryo or fruitlet [ 6 ]. The developing seed in young fruitlets is believed to repress flower induction in vegetative buds via phytohormones and removal of fruitlets at the 3–18 mm fruit size, through thinning practices have been shown to lead to a more consistent flower formation (return bloom) for the following season [ 3 , 7 , 8 ]. There have been investigations of other factors that influence flower formation in apple such as stress associated with temperature, photoperiod [ 9 , 10 ], water deficit as well as internal factors associated with carbon-nitrogen ratio, hormones and interaction with other organs (leaves, terminal shoot growth, and fruit) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The root phenotype may confer direct resilience to root pest and pathogens ( Cháves-Gómez et al, 2020 ) as well as to abiotic stresses ( He et al, 2020 ; Martínez-García et al, 2020 ) such as drought, flooding, and salt soil conditions ( Gautier et al, 2019 ). Rootstocks can also induce less trivial scion morphological changes such as dwarfing and precocity, and even alter yield traits ( Egea et al, 2004 ; Picolotto et al, 2010 ; Madam et al, 2011 ; Expósito et al, 2020 ; Kviklys and Samuolienė, 2020 ). Rootstock effects can go further and influence properties typically attributed to the clonal scion such as fruit sensorial and nutritional quality—e.g., texture, sugar content, acidity, pH, flavor, and color ( Giorgi et al, 2005 ; Gullo et al, 2014 ; Balducci et al, 2019 ), cold tolerance and shoot pest and pathogen resistance ( Rubio et al, 2005 ; Goldschmidt, 2014 ).…”
Section: Introductionmentioning
confidence: 99%